Project ICOPE Brazil: a study on the intrinsic capacity of Brazilian older adults and accuracy of the screening tool proposed by the World Health Organization - Eduardo Ferriolli; Roberto Alves Lourenço; Vitor Pelegrim de Oliveira; Renato Gorga Bandeira de Mello; Renata Eloah de Lucena Ferretti-Rebustini; Wilson Jacob Filho; Núcleo de Pesquisa sobre o Envelhecimento e o Idoso (NAPENV) (Brazilian Society of Geriatrics and Gerontology, 2023)
None.